Model Pendidikan Islam Progresif - Idris, Muh; Mokodenseho, Sabil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Islamic education is a future choice, and a reference in developing human potential and the embryo of world civilization. However, Islamic education does not always run smoothly, and in fact, it seems static because the education that is carried out cannot be separated from the system and the laws of life that take place. Therefore, Islamic education must be managed in a professional and quality manner. This paper aims to offer a progressive Islamic education model. Through literature studies from various literatures, which are then described and analysed with a qualitative approach, it shows that the Islamic education model must be designed and oriented towards empowering and developing human potential, so as to produce competitive and productive Human Resources. The basic models and styles of progressive Islamic education are able to create positive forces that can influence and determine human attitudes in life. The stronger the quality and potential of the human person, the more they will be able to have a visionary perspective and be able to realize and deepen the meaning of Islamic education in life as a determinant of identity. Thus, the Islamic education system will immediately be reformulated in accordance with the dynamics of the times, market needs, and based on local wisdom.